2018
DOI: 10.1002/ijc.31748
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations in specific and connected subpathways are associated with short neuroblastoma patients’ survival and indicate proteins targetable at onset of disease

Abstract: Neuroblastoma (NB) is an embryonic malignancy of the sympathetic nervous system with heterogeneous biological, morphological, genetic and clinical characteristics. Although genomic studies revealed the specific biological features of NB pathogenesis useful for new therapeutic approaches, the improvement of high-risk (HR)-NB patients overall survival remains unsatisfactory. To further clarify the biological basis of disease aggressiveness, we used whole-exome sequencing to examine the genomic landscape of HR-NB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Additionally, inactivating somatic mutations in SMARCA4 have been reported in many cancer cell lines, including non-small cell lung cancer and small cell carcinoma of the ovary 21,22 . Recently, we and others have found SMARCA4 somatic point mutations in NB, highlighting its role in the oncogenesis of this neuroblastic tumor 7,23 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Additionally, inactivating somatic mutations in SMARCA4 have been reported in many cancer cell lines, including non-small cell lung cancer and small cell carcinoma of the ovary 21,22 . Recently, we and others have found SMARCA4 somatic point mutations in NB, highlighting its role in the oncogenesis of this neuroblastic tumor 7,23 .…”
Section: Discussionmentioning
confidence: 78%
“…Genome-wide association studies, high-throughput sequencing and microarray gene expression-based studies have identified multiple genetic changes that characterize NB -both hereditable and somatically acquired [6][7][8][9][10][11] . Genetic alterations occurring in noncoding DNA such as TERT rearrangements 12 and point mutations in regulatory elements of transcription factor binding sites 13 also contribute to NB development.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review regarding RND3 specifically evaluated the pro- and anti-cancer functions and concluded that indeed, the overall impact of RND3 is context dependent [28]. Mutation of SLC12A1 has been associated with a short survival in NBL [29]. POF1B has no known, previous connection to NBL and little connection to cancer in general.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing studies of neuroblastoma have documented low somatic mutation rates and few recurrently mutated genes. Indeed, only mutations in ALK, ATRX, and TERT have been identified as the most frequent genetic abnormalities (9)(10)(11)(12). Recent studies have shown that disease-associated genomic variation is commonly located in regulatory elements in the human population (13).…”
Section: Introductionmentioning
confidence: 99%